2015
DOI: 10.1371/journal.pone.0130866
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual Behaviors, HIV Knowledge, and Stigmatizing/Discriminatory Attitudes among Men Who Have Sex with Men

Abstract: ObjectiveTo assess the correlates for bisexual behaviors, HIV knowledge, and HIV/AIDS-related stigmatizing/discriminatory attitudes among men who have sex with men (MSM).MethodsA cross-sectional survey among MSM was conducted in 2011 to provide demographics, sexual behaviors, HIV knowledge, HIV/AIDS-related stigmatizing/discriminatory attitudes, and services in Jinan, Qingdao, and Yantai of Shandong Province of China.ResultsOf 1230 participants, 82.8% were single, 85.7% aged <35 years, and 47.2% received colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
5
14
0
Order By: Relevance
“…In our study, those with better schooling presented greater HIV/AIDS knowledge, in agreement with studies conducted in Brazil and in other countries 19,21,[25][26][27]35 . It is also noteworthy the association between high level of knowledge, being white, and having private health insurance -important proxy variables that indicate belonging to higher social strata.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, those with better schooling presented greater HIV/AIDS knowledge, in agreement with studies conducted in Brazil and in other countries 19,21,[25][26][27]35 . It is also noteworthy the association between high level of knowledge, being white, and having private health insurance -important proxy variables that indicate belonging to higher social strata.…”
Section: Discussionsupporting
confidence: 92%
“…Few variables related to health services remained associated with high level of knowledge in the multivariate analysis: previous syphilis testing and having received educational material on STI. In the literature, both, previous HIV testing and having had an STI diagnosis, have been associated with a higher level of knowledge 21,[25][26][27] . STI/HIV testing seems to be an opportunity to disseminate information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey from Jinan, Qingdao, and Yantai of Shandong province in China concluded that the bisexual behaviour is independently associated with higher levels of HIV/AIDS-related discrimination [33]. Social ( P  < 0.001) and spirituality ( P  = 0.049) domains, and total HRQoL ( P  < 0.001) were predicted by perceived discrimination.…”
Section: Discussionmentioning
confidence: 99%